ADVERTISING ON EARNED MEDIA IN SOCIAL MEDIA: SYSTEMATIC LITERATURE REVIEW - Deniswara, Fre Derik P.; Afifa, Nurul Hildha; Munawar, Moh. Hefni (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2024)
Earned media is a marketing strategy that gets results naturally without the need to spend money to attract users through paid advertising or branding of owned media. This research method uses Systematic Analysis (SLR) which is a specialized research method to collect and evaluate research relevant to a particular focus and topic. The purpose of SLR is to identify various perspectives related to the subject under study and determine the strategies that will be used to help overcome the problems that arise. Researchers use various library sources and their variations to obtain the necessary data or information. By utilizing existing reference sources, writing this scientific article can be done smoothly. Data collection is done by documenting all articles that have similar research to the research report. There are 10 articles from reputable journals used in this research. Thus, this research not only provides academic contributions in the field of marketing, but also provides practical benefits for companies that want to utilize earned media as part of their marketing strategy.